2017
DOI: 10.3390/w9100770
|View full text |Cite
|
Sign up to set email alerts
|

Sunshine Duration Variability in Haihe River Basin, China, during 1966–2015

Abstract: Sunshine can have a profound impact on the systematic change in climate elements, such as temperature and wind speed, and in turn affects many aspects of the human society. In recent years, there has been a substantial interest in the variation of sunshine duration due to the dramatic global climate change. Hence, there is a need to better understand the variation of sunshine duration in order to cope with climate change. This study aimed to analyze the variation of sunshine duration in Haihe River basin, Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…There are generally few studies on the influential climatic factors in China. In this study, Win played a significant role in driving SD in HHB, and Pre prevailed in TMB from 1959 to 2017; these findings are in accordance with those of previous studies (You et al ., 2010; Ren et al ., 2017). Our results are generally in agreement with most previous studies, suggesting the rationality and reliability of this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are generally few studies on the influential climatic factors in China. In this study, Win played a significant role in driving SD in HHB, and Pre prevailed in TMB from 1959 to 2017; these findings are in accordance with those of previous studies (You et al ., 2010; Ren et al ., 2017). Our results are generally in agreement with most previous studies, suggesting the rationality and reliability of this study.…”
Section: Resultsmentioning
confidence: 99%
“…Observations from a total of 839 meteorological stations throughout mainland China recorded by Campbell‐Stokes were collected for the SD data set. Such data set underwent rigorous quality processing and checks, which guarantees the consistency of the data (Ren et al ., 2017). Other climatic variables such as atmosphere pressure (Prs, Kpa), vapour pressure (Vp, Kpa), precipitation (Pre, mm), relative humanity (Rhu, %), and wind speed (Win, m⋅s –1 ) were also obtained from the CMA with the same 839 stations, and the data set quality was strictly controlled by the CMA (Wang et al ., 2017b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors attributed to the decrease in sunshine duration and wind speed also vary among studies [36,[80][81][82]. For sunshine duration, multiple studies have concluded that this decrease may be related to the increase in aerosols and other air pollutants [3,83]. In other studies, it is argued that the decrease may be related to the increase in cloud cover.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the temporal trend is analyzed by using linear trend analysis, mutation test, and significance test, and Universal Kriging spatial interpolation method was used to analyze spatial changes (Hu et al, 2003;Ren et al, 2017). Mann-Kendall (M-K) nonparametric test can be very effective for testing time series (Kendall, 1948).…”
Section: Time Series Analysis Methodsmentioning
confidence: 99%